Determining the burden of the family caregivers of people with neuromuscular diseases who use a wheelchair. Issue 24 (June 2018) - Pousada, Thais; Groba, Betania; Nieto-Riveiro, Laura; Pazos, Alejandro; Díez, Emiliano; Pereira, Javier
Abstract : Abstract: The present study provides a basic outline of the care and support that family caregivers offer to people affected by neuromuscular diseases. To determine the presence of burden in caregivers of people with neuromuscular diseases who use a wheelchair and to establish whether the presence of burden is influenced by contextual factors, between them, the use of wheelchair. The applied design was cross-sectional and descriptive. The data were collected through a specific questionnaire, the Functional Independence Measure, the Matching Person and Technology form and the Zarit Burden Interview. The caregiver burden was analyzed in relation to different characteristics of the affected people, their wheelchairs, and factors related to the family caregivers themselves. The sample consisted of 41 caregivers, most of them (78.1%) being parents of the affected people. The burden was detected in 71.7% of caregivers. The level of dependence was not related to the presence of burden. Performing care work affected carers' physical health (80.5%), their mood (68.3%), and reduced their leisure time (90.2%). The type of wheelchair and the frequency of its use were not related to the burden. The results suggest that caregivers perceive burden, but its intensity is not related to the seriousness of the disease of the care receiver.